Tunable polyesterification of xylitol: from linear to crosslinked structures (2017)
The copolymerization by condensation chemistry of succinic acid and xylitol, a byproduct from the sugarcane and alcohol industry, is reported. Two methodologies were studied concerning succinic acid, with and without carboxylic acid activation, yielding crosslinked and linear low molecular weight polymers, respectively. All polymerizations were carried out at reaction times in the range from 36 to 80 h, with a molar mass ratio of 1:1 and 1:3. Linear and crosslinked polyesters were analyzed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, DSC and TGA, and structural characterization was carried out by Fourier transform infrared spectroscopy and NMR. © 2016 Society of Chemical Industry. © 2016 Society of Chemical Industry